Chemical constituents in the rhizome of Curcuma longa and the pharmacological importance of curcumin hybrids - A. Jerin Rex; P. Parthiban (Medicinal Chemistry Research, 2026)

Dietary supplementation of Durvillaea potatorum fucoidan enhances the immune responses and improves survival of juvenile black tiger shrimp Penaeus monodon against white spot syndrome virus and acute hepatopancreatic necrosis disease - Joseph P. Faisan; Rex Ferdinand M. Traifalgar; Leobert D. de la Peña; Valeriano L. Corre; Mary Jessa Bell B. Pagapulan; Vyenge Erre D. Gayosa (Aquaculture International, 2026)

Recent advances in piperidones as privileged scaffolds for drug discovery and development - A. Jerin Rex; P. Parthiban (Medicinal Chemistry Research, 2026)

P30-81 High-throughput RNA sequencing (Transcriptomics) combined with multiparametric New Approach Methodologies (NAMs) for cardiotoxicity risk assessment and mechanistic determination - J. Eakins; C. Bruhn; A. Rosell-Hildago; R. Rex; D. Yuezak; M. Fernandes dos Reis; T. Samatov; A. Hackmann; G.R. Aquino; C. Vogeley; N. Sahini; G. Goussarov; et al. (Toxicology Letters, 2025)

Colloidal Nafion morphology in 1,2-alkanediols and its impact on membrane and ionomer properties - Jeffrey M. Klein; Danah Kim; Cynthia Welch; Rex P. Hjelm; Marilyn E. Hawley; Anna Sokolova; Sung-Dae Yim; Natalia Macauley; Hui Xu; Sara Pedram; Jasna Jankovic; Seung Geol Lee; et al. (Chemical Engineering Journal, 2025)

Unravelling the origins of shale nanoporosity using small-angle neutron scattering (SANS) - Chelsea W. Neil; Rex P. Hjelm; Andrew Strzelecki; Michael Cheshire; Jon Burger; Lilin He; Hongwu Xu (Fuel, 2025)

P06-21 Multiparametric in vitro assays combined with high-throughput RNA sequencing for cardiotoxicity risk assessment and mechanistic insight - S. Llewellyn; A. Rosell-Hidalgo; C. Bruhn; K. Headspith; T. Samatov; A. Hackmann; G.R. Aquino; M. Fernandes dos Reis; R. Rex; D. Yuezak; C. Vogeley; N. Sahini; et al. (Toxicology Letters, 2024)

A signaling network map of Lipoxin (LXA4): an anti-inflammatory molecule - G. P. Suchitha; Rex Devasahayam Arokia Balaya; T. S. Keshava Prasad; Shobha Dagamajalu (Inflammation Research, 2024)

Sediment–water exchange and risk assessment of pesticidal persistent organic pollutants in Bharathappuzha and Periyar Riverine region along the Arabian Sea - K. Ronnie Rex; P. G. Vinod; K. S. Praveen; Paromita Chakraborty (Environmental Geochemistry and Health, 2024)

Co-pyrolysis of real-world plastics polystyrene, polypropylene and low-density polyethylene, its thermal behaviour and kinetic studies - P. Rex; L. R. Miranda (International Journal of Environmental Science and Technology, 2024)

Reproductive quality evaluation of male Indian white prawn Penaeus indicus broodstock fed diets supplemented with polychaete extracts ( Marphysa sp.) - Sheryll S. Santander-Avanceña; Rex Ferdinand M. Traifalgar; Erish G. Estante-Superio; Steve P. Janagap; Roger Edward P. Mamauag; Harold M. Monteclaro; Liberato V. Laureta; Gerald F. Quinitio (Invertebrate Reproduction & Development, 2023)

The effect of salinity on the pressure susceptibility of the NF270 membrane - Oliver P. Crossley; Rex B. Thorpe; Dominik Peus; Judy Lee (Desalination, 2023)

Prospective review for development of sustainable catalyst and absorbents from biomass and application on plastic waste pyrolysis - P. Rex; V. Ganesan; V. Sivashankar; S. Tajudeen (International Journal of Environmental Science and Technology, 2023)

Nonlinear finite element modeling and experimental investigation of SFRC beams strengthened with GFRP laminate under static loading - L. K. Rex; P. N. Raghunath; K. Suguna (Innovative Infrastructure Solutions, 2022)

Year-round acoustic monitoring of Antarctic blue and fin whales in relation to environmental conditions off the west coast of South Africa - Ishmail S. Letsheleha; Fannie W. Shabangu; Dara Farrell; Rex K. Andrew; Philip L. la Grange; Ken P. Findlay (Marine Biology, 2022)

Fine‐scale phylogeography of coastal fishes in the South China Sea: Possible roles of biological traits and geography - Nozomu Muto; Ryo Kakioka; Mazlan Abd Ghaffar; Nguyen Van Quan; Veera Vilasri; Rex F. M. Traifalgar; Ricardo P. Babaran; Fumihito Muto; Hirohiko Takeshima; Hiroyuki Motomura; Satoshi Ishikawa (Journal of Biogeography, 2021)
Aim Although the underlying biotic and abiotic factors of phylogeographic patterns is an important topic in biogeography, they remain largely unexplored in marine fishes. We empirically investigated the effects of several biological traits on phylogeographic patterns of selected marine fishes. We predict that overall similarity in these traits correlates with similarity in phylogeographic patterns among species, and that genetic diversity and demographic stability are associated with these traits, as well as the local (paleo)environment. Location Five localities in the South China Sea (SCS). Taxon Thirteen species of coastal marine fishes. Methods Phylogeographic Concordance Factors (PCFs) based on mitochondrial DNA sequences were tested for correlation with similarity based on distribution range, depth of occurrence, habitat preference, salinity tolerance and fecundity among the subset of the focal species. The relationship between phylogeographic patterns and these traits was also qualitatively examined. Bayesian model averaging was used to test the association between these traits and the genetic diversity estimates. Results Pairwise PCFs of five species across all localities were correlated with pairwise biological similarity, with depth and distribution ranges contributing most to the biological similarity. Nucleotide diversity of Indo‐west Pacific species tended to be greater than that of circumtropical species. Populations showing signs of demographic expansions were concentrated in three localities. A novel concordant population break across six focal species and other marine organisms coincided with the dispersal barrier previously suggested by biophysical dispersal modelling. Main conclusions Abiotic factors were dominant in controlling phylogeographic patterns, with possible contributions from biotic factors. Depth and distribution ranges, or other eco‐physiological traits underlying these, might have influenced the phylogeographic patterns of several species, presumably coupled with historical vicariance. The geography of local populations relative to the shallow continental shelf may explain the heterogeneous demography. Historical vicariance and contemporary ocean currents have contributed to the concordant population break.

Temperature-responsive PNDJ hydrogels provide high and sustained antimicrobial concentrations in surgical sites - Derek J. Overstreet; Vajra S. Badha; John M. Heffernan; Erin P. Childers; Rex C. Moore; Brent L. Vernon; Alex C. McLaren (Drug Delivery and Translational Research, 2019)

The successful uptake and sustainability of rapid infectious disease and antimicrobial resistance point-of-care testing requires a complex ‘mix-and-match’ implementation package - John P. Hays; Konstantinos Mitsakakis; Saturnino Luz; Alex van Belkum; Karsten Becker; Ann van den Bruel; Stephan Harbarth; John H. Rex; Gunnar Skov Simonsen; Guido Werner; Valentina Di Gregori; Gerd Lüdke; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Small ad hoc versus large general training populations for genomewide selection in maize biparental crosses - Sofía P. Brandariz; Rex Bernardo (Theoretical and Applied Genetics, 2019)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

Cryptic genetic divergence in Scolopsis taenioptera (Perciformes: Nemipteridae) in the western Pacific Ocean - Ryo Kakioka; Nozomu Muto; Hirohiko Takeshima; Arnold C. Gaje; Ramon S. Cruz; Ulysses B. Alama; Armi May T. Guzman; Rex Ferdinand M. Traifalgar; Ricardo P. Babaran; Osman Muda; Wahidah Mohd Arshaad; Sukchai Arnupapboon; et al. (Ichthyological Research, 2018)

Rapid and cost-effective molecular identification of the three mackerel species of the genus Rastrelliger (Perciformes: Scombridae) using PCR-RFLP analysis - Nozomu Muto; Hirohiko Takeshima; Ryo Kakioka; Ulysses B. Alama; Armi May T. Guzman; Ramon S. Cruz; Arnold C. Gaje; Rex Ferdinand M. Traifalgar; Hiroyuki Motomura; Fumihito Muto; Ricardo P. Babaran; Satoshi Ishikawa (Marine Biodiversity, 2017)

Genetic and morphological differences among the three species of the genus Rastrelliger (Perciformes: Scombridae) - Nozomu Muto; Ulysses B. Alama; Harutaka Hata; Armi May T. Guzman; Ramon Cruz; Arnold Gaje; Rex Ferdinand M. Traifalgar; Ryo Kakioka; Hirohiko Takeshima; Hiroyuki Motomura; Fumihito Muto; Ricardo P. Babaran; et al. (Ichthyological Research, 2016)

Molecular Detection of New Delhi Metallo-Beta-Lactamase-1 (NDM-1) Positive Bacteria from Environmental and Drinking Water Samples by Loop Mediated Isothermal Amplification of bla NDM-1 - P. Rathinasabapathi; Deepak S. Hiremath; Rex Arunraj; M. Parani (Indian Journal of Microbiology, 2015)

A genome- and phenome-wide association study to identify genetic variants influencing platelet count and volume and their pleiotropic effects - Khader Shameer; Joshua C. Denny; Keyue Ding; Hayan Jouni; David R. Crosslin; Mariza de Andrade; Christopher G. Chute; Peggy Peissig; Jennifer A. Pacheco; Rongling Li; Lisa Bastarache; Abel N. Kho; et al. (Human Genetics, 2014)

Editorial - P. Srinivasa Rao; Rex B. Demafelis (Sugar Tech, 2013)

Elevated species diversity in abyssal gastropods off Newfoundland: the potential role of food supply - Carol T. Stuart; Michael A. Rex; Derek P. Tittensor; Craig R. Smith (Marine Biodiversity, 2011)

Understanding the relation between Arctic ozone loss and the volume of polar stratospheric clouds - N. R. P. Harris; R. Lehmann; M. Rex; P. Von Der Gathen (International Journal of Remote Sensing, 2009)

Inferring the diversification of the epiphytic fern genus Serpocaulon (Polypodiaceae) in South America using chloroplast sequences and amplified fragment length polymorphisms - H.-P. Kreier; M. Rex; K. Weising; M. Kessler; A. R. Smith; H. Schneider (Plant Systematics and Evolution, 2008)

Multicenter retrospective development and validation of a clinical prediction rule for nosocomial invasive candidiasis in the intensive care setting - L. Ostrosky-Zeichner; C. Sable; J. Sobel; B. D. Alexander; G. Donowitz; V. Kan; C. A. Kauffman; D. Kett; R. A. Larsen; V. Morrison; M. Nucci; P. G. Pappas; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

International, open-label, noncomparative, clinical trial of micafungin alone and in combination for treatment of newly diagnosed and refractory candidemia - L. Ostrosky-Zeichner; D. Kontoyiannis; J. Raffalli; K. M. Mullane; J. Vazquez; E. J. Anaissie; J. Lipton; P. Jacobs; J. H. Jansen Rensburg; J. H. Rex; W. Lau; D. Facklam; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Regional landslide-hazard assessment for Seattle, Washington, USA - Rex L. Baum; Jeffery A. Coe; Jonathan W. Godt; Edwin L. Harp; Mark E. Reid; William Z. Savage; William H. Schulz; Dianne L. Brien; Alan F. Chleborad; Jonathan P. McKenna; John A. Michael (Landslides, 2005)

International, open-label, noncomparative, clinical trial of micafungin alone and in combination for treatment of newly diagnosed and refractory candidemia - L. Ostrosky-Zeichner; D. Kontoyiannis; J. Raffalli; K. M. Mullane; J. Vazquez; E. J. Anaissie; J. Lipton; P. Jacobs; J. H. Jansen Rensburg; J. H. Rex; W. Lau; D. Facklam; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Identification and enumeration of bacteria assimilating dimethylsulfoniopropionate (DMSP) in the North Atlantic and Gulf of Mexico - Rex R. Malmstrom; Ronald P. Kiene; David L. Kirchman (Limnology and Oceanography, 2004)
The algal‐derived compound dimethylsulfoniopropionate (DMSP), which is the precursor of the climatically active gas dimethylsulfide, is potentially an important source of carbon and sulfur to marine bacterioplankton. Currently, bacteria of the Roseobacter clade, a subgroup of ά;‐proteobacteria, are hypothesized to be the key participants in the metabolism of DMSP. To test this hypothesis, we used a combination of microautoradiography and fluorescence in situ hybridization (Micro‐FISH) to identify the bacteria assimilating 35 S DMSP in the Gulf of Mexico, the Gulf of Maine, and the Sargasso Sea. On average, half of the bacterial community assimilated DMSP in these environments. Members of the ά‐proteobacteria dominated DMSP assimilation, accounting for 35–40% of bacteria assimilating DMSP. Cytophaga ‐like bacteria andγ‐proteobacteria each accounted for 15–30% of DMSP‐assimilating cells. The ά‐proteobacteria accounted for a greater fraction of the DMSP‐assimilating community than expected based on their overall abundance, whereas Cytophaga ‐like bacteria were typically underrepresented in the DMSP‐assimilating community. Members of the Roseobacter clade assimilated more DMSP on a per‐cell basis than any other group, but they did not account for most of the DMSP assimilation, nor were they always present even when DMSP turnover was high. These results indicate that the biogeochemical flux of dissolved DMSP is mediated by a large and diverse group of heterotrophic bacteria.

Dinoflagellate cyst assemblages as tracers of sea‐surface conditions in the northern North Atlantic, Arctic and sub‐Arctic seas: the new ‘ n = 677’ data base and its application for quantitative palaeoceanographic reconstruction - Anne de Vernal; Maryse Henry; Jens Matthiessen; Peta J. Mudie; André Rochon; Karin P. Boessenkool; Frédérique Eynaud; Kari GrØsfjeld; Joël Guiot; Dominique Hamel; Rex Harland; Martin J. Head; et al. (Journal of Quaternary Science, 2001)
The distribution of dinoflagellate cyst (dinocyst) assemblages in surface sediment samples from 677 sites of the northern North Atlantic, Arctic and sub‐Arctic seas is discussed with emphasis on the relationships with sea‐surface parameters, including sea‐ice cover, salinity and temperature of the coldest and warmest months. Difficulties in developing a circum‐Arctic data base include the morphological variation within taxa (e.g. Operculodinium centrocarpum , Islandinium ? cezare and Polykrikos sp.), which probably relate to phenotypic adaptations to cold and/or low salinity environments. Sparse hydrographical data, together with large interannual variations of temperature and salinity in surface waters of Arctic seas constitute additional limitations. Nevertheless, the use of the best‐analogue technique with this new dinocyst data base including 677 samples permits quantitative reconstruction of sea‐surface conditions at the scale of the northern North Atlantic and the Arctic domain. The error of prediction calculated from modern assemblages is ±1.3 °C and ±1.8 °C for the temperature of February and August, respectively, ±1.8 for the salinity, and ±1.5 months yr −1 for the sea‐ice cover. Application to late Quaternary sequences from the western and eastern subpolar North Atlantic (Labrador Sea and Barents Sea) provide reconstructions compatible with those obtained using the previous dinocyst data base ( n = 371), which mainly included modern data from the northern North Atlantic. Copyright © 2001 John Wiley & Sons, Ltd.

A Comparison of Match Ozonesonde-Derived and 3D Model Ozone Loss Rates in the Arctic Polar Vortex during the Winters of 1994/95 and 1995/96 - I. Kilbane-Dawe; N. R. P. Harris; J. A. Pyle; M. Rex; A. M. Lee; M. P. Chipperfield (Journal of Atmospheric Chemistry, 2001)

Characteristics of human dendritic cells generated in a microgravity analog culture system - Cherylyn A. Savary; Monica L. Grazziutti; Donna Przepiorka; Stephen P. Tomasovic; Bradley W. McIntyre; Darren G. Woodside; Neal R. Pellis; Duane L. Pierson; John H. Rex (In Vitro Cellular & Developmental Biology - Animal, 2001)

The Introduction of Postconsumer Recycled Material into TYVEK® Production, Marketing, and Organizational Challenges - Mark P. Sharfman; Rex T. Ellington; Mark Meo (Journal of Industrial Ecology, 2001)
Summary In the late 1980s, with the advent of increased consumer environmental awareness, DuPont faced a challenge with its TYVEK® family of nonwoven polyethylene textile products. TYVEK is used in a wide variety of applications ranging from house wrap to medical packaging. One of the most visible portions of the business is envelopes used by FedEx (previously known as Federal Express), the wellknown courier and delivery service and by the U.S. Postal Service. As early as 1988, end users began asking questions about the environmental characteristics of TYVEK envelopes. As these questions increased, DuPont began to address the concerns directly. In response to the market's concern and because of the increased availability of postconsumer‐recycled (PCR) polyethylene, DuPont decided to put PCR polyethylene into TYVEK, beginning with the envelope business. Further, DuPont developed a recycling infrastructure for TYVEK because, although TYVEK consists entirely of high‐density polyethylene, which is highly recyclable, no infrastructure was in place to recycle the material. These decisions produced a wide variety of technical and organizational challenges the firm had to overcome. This case study examines how DuPont made these choices and overcame the difficulties created by implementing needed changes. Whereas the envelope market for TYVEK embraced PCR polyethylene, other product markets resisted the innovation. The article closes with a discussion of the lessons learned from DuPont's experience.

CHARACTERISTICS OF HUMAN DENDRITIC CELLS GENERATED IN A MICROGRAVITY ANALOG CULTURE SYSTEM - CHERYLYN A. SAVARY; MONICA L. GRAZZIUTTI; DONNA PRZEPIORKA; STEPHEN P. TOMASOVIC; BRADLEY W. McINTYRE; DARREN G. WOODSIDE; NEAL R. PELLIS; DUANE L. PIERSON; JOHN H. REX (In Vitro Cellular & Developmental Biology - Animal, 2001)

Chemical Ozone Loss in the Arctic Winter 1994/95 as Determined by the Match Technique - M. Rex; P. Von Der Gathen; G.O. Braathen; N.R.P. Harris; E. Reimer; A. Beck; R. Alfier; R. Krüger-carstensen; M. Chipperfield; H. De Backer; D. Balis; F. O'Connor; et al. (Journal of Atmospheric Chemistry, 1999)

A Study of Ozone Laminae Using Diabatic Trajectories, Contour Advection and Photochemical Trajectory Model Simulations. - S. J. Reid; M. Rex; P. Von Der Gathen; I. Fløisand; F. Stordal; G. D. Carver; A. Beck; E. Reimer; R. Krüger-Carstensen; L. L. De Haan; G. Braathen; V. Dorokhov; et al. (Journal of Atmospheric Chemistry, 1998)

Subaqueous, basaltic lava dome and carapace breccia on King George Island, South Shetland Islands, Antarctica - J. L. Smellie; I. L. Millar; P. J. Butterworth; D. C. Rex (Bulletin of Volcanology, 1998)

Combination of non-isotopic in situ hybridisation with detection of enzyme activity, bromodeoxyuridine incorporation and immunohistochemical markers - Maria Rex; Richard Church; Kevin Tointon; P. J. Scotting (Histochemistry and Cell Biology, 1997)

A Framework for Information Systems in Life‐Cycle‐Oriented Environmental Management - Teresa M. Shaft; Rex T. Ellington; Mark Meo; Mark P. Sharfman (Journal of Industrial Ecology, 1997)
Summary Although business firms have improved their environmental performance, a variety of forces are pushing businesses toward adopting environmental management throughout the entire life cycle of their products and processes. In this article we discuss the information systems elements of an environmental management approach we call “life‐cycle‐oriented environmental management” (LCOEM).This approach requires the firm to manage the effects of its processes from the creation of inputs to the final disposal of outputs, that is, from cradle to grave. We present a framework of the classes of information systems needed, describe their use in an LCOEM setting and define their inter relationships. We conclude with a discussion of the implications of LCOEM information systems.